Brain networks and medical education - Prineethi, Sheena; Bharath, Rose Dawn; A., Thamodharan; Mani, Sunithi (International Journal of Scientific Reports, 2021)
Background: There has been significant progress in understanding the human brain with the development of modalities like functional magnetic resonance imaging (fMRI), positron emission tomography (PET) etc. Education is an important source of intellectual, emotional and cultural stimulus to the brain. In this resting fMRI study, we aim to map out specific regions in the brain in which changes occur relating to memory, language, motor, behavioural and cognitive functions after five years of undergraduate medical education and how this knowledge can bring us closer to understanding the brain and its functions and applications in clinical practice. Methods: A total number of 48 normal, healthy medical students from our medical college were included in the study, and were divided into two groups, the first group completed five years of under-graduate medical training and the second group consisted of individuals who had only 4 months of exposure to medical training. Resting state fMRI study was performed and seed-to-voxel based functional connectivity analysis method was used to derive between group differences Results: Out of the 48, 13 played one or more sport professionally, 8 were musically oriented with skills to play one or more musical instrument professionally and 9 had other talents (2-Good academic, 2-theatre, 3-dancing, 2-art like pottery and painting). Conclusions: There were significant differences in the right inferior temporal gyrus which is the seat of many cognitive functions like language, emotion and memory and the left cerebellar hemisphere, which is known to play a role in fine motor functions, language and visual learning.